Exercise Evaluation and Prescription—2nd Edition (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
“Exercise Evaluation and Prescription—Second Edition” presents papers focusing on team sports (soccer, volleyball, handball, rugby, and basketball), individual sports (cycling, running, weightlifting, and Paralympic powerlifting), diseases (in overweight, obese, and postmenopausal women with type 2 diabetes mellitus; individuals with pulmonary embolism; individuals with cardiovascular disease or its risk factors; individuals receiving β-blocker treatment; and breast cancer survivors), healthy individuals, and murine models.